Frictional Resistance in Orthodontics-A Review - Hiba A.Kamel / Shaym Sh. Taha ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
During orthodontic treatment, sliding mechanics are frequently used. This mechanic has some drawbacks, one of which is the friction that is formed at the bracket/archwire interference, which may reduce the amount of desirable orthodontic movement achieved. Friction is the resistance to motion that occurs when one object travels tangentially against another.Friction is classified into two types: static and kinetic. In order for one object to slide over another, the force provided must be greater than the frictional resistance created.Frictional resistance between archwire and brackets is caused by a variety of physical and biological reasons.